Faktor yang Mempengaruhi Keputusan Perempuan Berstatus Menikah Untuk Bekerja di Kelurahan Bukit Pinang Kota Samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this study was to determine the Decision Factors Affecting Women Have status Married To Work. The theory used in this research is the theory of human resources, population and employment. This research uses primary data obtained from the questionnaire in the village of Bukit Pinang Samarinda City assisted with village monographs information on Bukit Pinang 2015. The analysis method used in this study is Binary Logistic and processed using SPSS (Statistical Programme For Science) version 20. From the data that I can conclude that 1) The education level of the wife against the decision of a wife's work shows its p value of 0.005, which means indicates a positive influence and significant. 2) Income husband against a wife's decision to work shows the p value for 0000 which means showing negative influence and significant. 3) Number of dependents to the decision of the wife's work shows the p value of 0992 which means that indicates the effect is negative but not significant.Keywords: dependents and decision Wife